Influência da espessura da infraestrutura em Zircônia (3Y-TZP)na resistência mecânica da porcelana de cobertura - Lungareze, Daniel [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Considering the possible effect of the cooling delaying of zirconia (3Y-TZP) in anatomical framework for higher volume, this study evaluated the influence of the framework thickness in the fracture load of porcelain veneered crowns, bond strength between zirconia and porcelain, hardness and fracture toughness of porcelain. For testing fracture load, maxillary first molar were prepared to accomplish three different thicknesses on the occlusal surfaces: Group I - 1 mm, Group II - 2 mm and Group III - 3 mm. The thickness of 1.1 ± 0.1 mm of porcelain VITA VM9 was applied by handmade technical stratification. The axial load was applied to the medial lingual cusp by means of a mechanical test machine (N = 45). The shear test was carried-out in flat plates (5 x 5 mm) in the three thicknesses of zirconia, and the porcelain was applied as cylindrical shape with 1,2 mm high for 4 mm in diameter (N=30). The shear bond strength test was performed by chisel. For measurement of the Vickers hardness and fracture toughness flat plates were fabricated as described above, and the porcelain was applied with uniform thickness of 1.2 mm (N=24). The measurements were done close to the surface and at the interface with zirconia. The mean and standard deviation for the test were: fracture load of the crowns (N) - GI = 1979 (523,5), GII = 2266 (816.9) and GIII = 2316 (672.9); sheer bond strength (MPa) - GI=18.5 (2.44), GII=15.6 (3.80) e GIII=17.1 (3.17); fracture toughness (MPa.m1/2) - GI = 1.53 and 1.48; GII = 1.89 and 1.70 - GIII = 1.84 and 1.72, respectively at the interface and close to the surface. Data from all trials analyzed by ANOVA were not significant for all the tests, revealing that the zirconia thicknesses did not affect the porcelain resistance of the crowns, hardness and fracture toughness and adhesion between the ceramic. Conclusion: The use...(Complete abstrat electronic access below)

Considerando o efeito das propriedades térmicas da zircônia (3Y-TZP) em infraestruturas anatômicas com maior volume, sobre a taxa de resfriamento da porcelana de cobertura e possível interferência sobre suas propriedades mecânicas, este estudo avaliou a influência da espessura da zircônia na resistência à fratura em coroas, dureza e tenacidade à fratura da porcelana e na resistência adesiva. Para o teste de resistência, foram obtidas infraestruturas em 3Y-TZP de coroas de 1º molar superior com três diferentes espessuras na oclusal: Grupo I - 1 mm, Grupo II - 2 mm e Grupo III - 3 mm. A porcelana VITA VM9 foi aplicada com espessura de 1,1 ± 0,1 mm pela técnica manual. A carga axial foi aplicada na cúspide mésiolingual por máquina de ensaios mecânicos (N=45). Para o teste de resistência de cisalhamento, foi aplicada a porcelana na forma cilíndrica com 1,2 mm de altura X 4 mm de diâmetro sobre placas de 3Y-TZP (5 x 5 mm) nas três espessuras (N= 30). O modo de falha foi analisado por microscopia óptica. Para medida da dureza Vickers e tenacidade à fratura da porcelana na interface com a 3Y-TZP e na superfície, foram usadas placas planas como descrito acima, e a porcelana aplicada, na extensão de uma das faces, com a espessura uniforme de 1,2 mm (N=24). Resultados: As médias e desvio padrão da resistência à fratura por compressão das coroas (N) foi: GI=1979 (523,5), GII=2266 (816,9) e GIII=2316 (672,9). A resistência ao cisalhamento (MPa) foi: GI=18,5 (2,44), GII=15,6 (3,80) e GIII=17,1 (3,17). A tenacidade à fratura (MPa.m1/2) foi: GI=1,53 e 1,48; GII=1,89 e 1,70 - GIII=1,84 e 1,72, respectivamente na interface e na superfície. ANOVA a um fator para resistência das coroas e ao cisalhamento, assim como a dois fatores para dureza e tenacidade a fratura não foram significantes. Concluiu-se que volumes...(Resumo completo clicar acesso eletrônico)
Keywords: Zircônio; Cerâmicas odontológicas; Reabilitação bucal; Propriedades físicas; Zirconium